Disparities between native americans and white individuals in global outcome trajectories over the 5 years after traumatic brain injury: A model systems study. - Jack D Watson; Paul B Perrin; Juan Carlos Arango-Lasprilla (PLoS ONE)
Purpose Traumatic brain injury (TBI) can lead to a host of challenges and negatively impacts Native Americans more than any other ethnic group in the U.S. Despite this, little research exists on Native Americans with TBI. The current study examined disparities in global outcome trajectories (overall level of function post-injury) between Native Americans and White individuals in the 5 years following TBI and whether sociodemographic or injury-related characteristics could account for this disparity. Method The current study used a sample of 75 Native Americans demographically matched by sex, age, and injury severity to 75 White individuals from the U.S. Traumatic Brian Injury Model Systems (TBIMS) database (n =  150). A series of hierarchical linear models (HLMs) was used to examine longitudinal global outcome trajectories between the two groups. Results Native Americans showed lower global outcome scores than their White counterparts with this difference worsening (i.e., growing larger) over time. The difference in scores and the differential movement over time were associated with differences between the ethnic groups in employment at the time of injury, substance use patterns, and type of insurance. Conclusion This study highlights the need for identification of and early intervention for risk factors that predict disparities in rehabilitation outcomes and points to the need for greater access to culturally informed care for Native Americans with TBI.